Strategic Management Of Integrated Resort With Casino To Sustain Competitive Advantage In Singapore - Tai, Siew Hoong (2008)
The purpose of this study is to propose and evaluate the business strategies for the upcoming Integrated Resorts (IRs) with casinos in Singapore. Strategic advantages and how they can be sustained in a longer run are investigated. Strategic management tools are adopted to assess the internal and external factors that could influence the sustainability and its potential success.